2019
DOI: 10.3847/1538-4357/ab08a1
|View full text |Cite
|
Sign up to set email alerts
|

The Mass–Metallicity Relation of Local Active Galaxies

Abstract: We systematically measure the gas-phase metallicities and the mass-metallicity relation of a large sample of local active galaxies for the first time. Observed emission-line fluxes from the Sloan Digital Sky Survey (SDSS) are compared to a four-dimensional grid of photoionization models using the Bayesian parameter estimation code NebulaBayes. For the first time we take into account arbitrary mixing between H II region and narrow-line region (NLR) emission, and the models are also varied with metallicity, ioni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 63 publications
11
45
0
Order By: Relevance
“…0, 8.40, 8,56, 8.69, 8.86, 9.00, respectively, Metallicity values in this range has been found for AGNs with redshifts varying from ∼ 0 to ∼ 7 (e.g. Nagao et al 2006a;Feltre, Charlot & Gutkin 2016;Matsuoka et al 2018;Thomas et al 2019;Mignoli et al 2019;Pérez-Montero et al 2019;Dors et al 2014Dors et al , 2015Dors et al , 2018. We found that photoionization models assuming (Z/Z⊙) > 2.0 produce similar intensities of N 2, therefore, only (Z/Z⊙) < = 2.0 were assumed in our analysis.…”
Section: Photoionization Modelsmentioning
confidence: 86%
“…0, 8.40, 8,56, 8.69, 8.86, 9.00, respectively, Metallicity values in this range has been found for AGNs with redshifts varying from ∼ 0 to ∼ 7 (e.g. Nagao et al 2006a;Feltre, Charlot & Gutkin 2016;Matsuoka et al 2018;Thomas et al 2019;Mignoli et al 2019;Pérez-Montero et al 2019;Dors et al 2014Dors et al , 2015Dors et al , 2018. We found that photoionization models assuming (Z/Z⊙) > 2.0 produce similar intensities of N 2, therefore, only (Z/Z⊙) < = 2.0 were assumed in our analysis.…”
Section: Photoionization Modelsmentioning
confidence: 86%
“…Looking from another perspective, Thomas et al (2019) found a systematic positive offset in the oxygen abundances for Seyfert galaxies in comparison to SFGs from the SDSS DR7. They inspect many possible methodological causes that could artificially create this offset.…”
Section: Mass-metallicity Relationmentioning
confidence: 94%
“…Our models predict a narrow range (see above) of O/H abundances and the large majority of our sample objects (∼ 99 per cent) shows 12 + log(O/H) values higher than 8.7 dex. A narrow metallicity range for AGNs, with 12+log(O/H) varying by ∼ 0.1 dex as a function of host galaxy stellar mass over the range 10.1 < ∼ log(M/M⊙) < ∼ 11.3, was also derived by Thomas et al (2019), who used the Bayesian parameter estimation code NebulaBayes. The derived narrow O/H range by the composite models for our sample reflects a stronger dependence of oxygen emission lines on shock parameters (e.g.…”
Section: Diagnostic Diagramsmentioning
confidence: 99%